C-Reactive Protein Levels in African Americans: A Diet and Lifestyle Randomized Community Trial - Hébert, James R. (2013)
BACKGROUND: Chronic Inflammation is linked to poor lifestyle behaviors and a variety of chronic diseases that are prevalent among African Americans, especially in the southeastern U.S. PURPOSE: The goal of the study was to test the effect of a community-based diet, physical activity, and stress reduction intervention conducted in 2009–2012 on reducing serum C-reactive protein (CRP) in overweight and obese African-American adults. METHODS: An RCT intervention was designed jointly by members of African-American churches and academic researchers. In late 2012, regression (i.e., mixed) models were fit that included both intention-to-treat and post hoc analyses conducted to identify important predictors of intervention success. Outcomes were assessed at 3 months and 1 year. RESULTS: At baseline, the 159 individuals who were recruited in 13 churches and had evaluable outcome data were, on average, obese (BMI=33.1 [±7.1]) and had a mean CRP level of 3.7 (±3.9) mg/L. Reductions were observed in waist-to-hip ratio at 3 months (2%, p=0.03) and 1 year (5%, p<0.01). In female participants attending ≥60% of intervention classes, there was a significant decrease in CRP at 3 months of 0.8 mg/L (p=0.05), but no change after 1 year. No differences were noted in BMI or interleukin-6. CONCLUSIONS: In overweight/obese, but otherwise “healthy,” African-American church members with very high baseline CRP levels, this intervention produced significant reductions in CRP at 3 and 12 months, and in waist-to-hip ratio, which is an important anthropometric predictor of overall risk of inflammation and downstream health effects. TRIAL REGISTRATION: This study is registered at www.clinicaltrials.gov NCT01760902.